Proteomic Analysis of Vibrio parahaemolyticus-Stimulated Pinctada martensii Proteins for Antimicrobial Activity, Potential Mechanisms, and Key Components - Haisheng Lin; Weiqiang Shen; Bei Luo; Wenhong Cao; Xiaoming Qin; Jialong Gao; Zhongqin Chen; Huina Zheng; Bingbing Song (Antibiotics, 2024)
Background: Bacterial infections are a major challenge in food processing and public health, and there is an urgent need to develop novel antimicrobial agents. Objectives: The purpose of this study is to investigate the potential mechanism and key components of Pinctada martensii antimicrobial proteins (Pm-Aps) to provide a theoretical basis for the development of novel antimicrobial agents. Methods: The researchers used Vibrio parahaemolyticus (VP) to stimulate Pinctada martensii, extracted the antimicrobial proteins, and analyzed their antimicrobial activities, potential mechanisms of action, and key components using proteomics. Results: The results showed that the antimicrobial activity of Pm-Aps, with broad-spectrum antimicrobial effects, was significantly enhanced after VP stimulation. This was associated with the upregulation of LAAO, CHDH, TLR2, ATG16L1, BAK, CLCA4, and CASP8 and the downregulation of MCM3, MCM5, DTYMK, PLK1, FBXO6, LPCAT3, GST, LAMTOR5, CYP17A, CTSA, and RRM1. It is hypothesized that these proteins may inhibit bacterial growth and multiplication by activating immune-related signaling pathways, inhibiting DNA replication and repair, and inducing apoptosis and autophagy. Furthermore, it was found that LAAO may be a key component of the antimicrobial action of Pm-Aps, killing bacteria by catalyzing the oxidation of amino acids to produce hydrogen peroxide (H2O2). Conclusions: These results strongly suggest that Pm-Aps is an effective antimicrobial protein, and it is expected that new LAAO can be obtained from Pm-Aps.